MEASURING THE IMPACT OF SOME INDICATORS AND TRADING VOLUME ON THE MARKET VALUE INDEX OF THE IRAQI STOCK EXCHANGE FOR THE PERIOD 2004-2023 (World Economics and Finance Bulletin, 2024)
The increase in the number of companies in trading and the number of work teams in the Iraq Stock Exchange Index, but the number of shares has an impact on the market index because of its importance, but in the increasing movement in the subscription, speculation, buying and selling market, and therefore the relationship between these companies, but there is no agreement on this. The absence of a relationship between data of the same degree and that they in place form those boundaries for Johansen, which indicates the existence of a long-term cocktail relationship between the participants. From the multiple linear regression equation, all the independent variables are not significant according to the (t) test except for one variable, that is, they do not affect the dependent variable except in a very small way, amounting to (28The number of shares traded is the indicator of the variable that has the most impact on the value in the Iraq Stock Exchange among the research variables. Thus, there is research into increasing the number of shares in company trading and trading sessions to raise the value of the market index. The research recommends increasing the number of shares in traded companies and trading sessions for the purpose of raising the market value index.
Keywords: Financial reports for the Iraqi Stock Exchange; financial stocks; financial investment